Little Roja Riding Hood - Elya, Susan Middleton, 1955- (G.P. Putnam's Sons, an imprint of Penguin Group (USA), 2014)
A rhyming twist on the classic fairy tale in which a little girl saves her grandmother from a wolf. Includes glossary of the Spanish words sprinkled throughout the text.